Land Use Planning for Soil Conservation and Watershed Management in Bundelkhand Region - Lal, Menhi; Singh, Panjab (Journal of Soil and Water Conservation, 2022)
Bundelkhand region is beset with problems of soil erosion, thin forest-cover and erratic-rainfall distribution. In this paper attempt has been made for the development of improved land use planning and alternate strategy through soil conservation and watershed management programmes.